The Effects of Physical Infrastructure Development in Supporting Economic Growth in North Sumatra Province - Indah Permata Sari (AIBPM Publisher, 2020)
The development of infrastructure in an area is a very important activity in the context of increasing economic growth. The development of infrastructure such as road, electricity and airport are also the activities that can encourage economic growth. This research was aimed to explain the effect of the construction of road, electricity and airport infrastructure on the economic growth of North Sumatra. This research was conducted by using quantitative research. The data of this study were sourced from BPS North Sumatra and Statistics Main Book starting from 2010-2018. The data was used the time series data with the process of data by using eviews 6. The results of this research indicated a positive influence between the development of physical infrastructure such as roads, electricity and airports on the economic growth of North Sumatra.